THE BUSINESS MANAGEMENT SKILLS OF SMALL INDUSTRIES ENTREPRENEURS AT CIBEUREUM DISTRICT SUKABUMI CITY - Muhyi, Herwan Abdul (AdBispreneur, 2017)
ABSTRACTThe City of Sukabumi is one of the city directly adjacent to Sukabumi Regency from the north, south, west and east. Potential major economies are from the industrial sector. This city does not have tourism potential of nature (natural tourism). In the industrial sector, the role of small businesses that have production activities play an important role in the economy of the city. The purpose of this study is to identify and explain the extent of the business management skills of small business entrepreneurs who perform production activities (small industries). This study describes the elements of business management skills that are run during this time. This study used a qualitative approach. This approach is intended to uncover the business management skills of small entrepreneurs in District of Cibeureum. To maintain the quality and validity of the data carried triangulation techniques. The results showed that the business management skills of small entrepreneurs in the district of Cibeureum not comply with management standards. This means that there are still many elements of the business management skills that does not run properly. The best element is the human relations while the lowest is the accounting.Keywords : Business management skills, small entrepreneurs  KETERAMPILAN PENGELOLAAN BISNIS PARA PENGUSAHA KECIL DI KECAMATAN CIBEUREUM KOTA SUKABUMI  ABSTRAK      Kota Sukabumi merupakan salah satu kota yang berbatasan langsung dengan Kabupaten Sukabumi baik dari sisi utara, selatan, barat dan timur. Potensi perekonomian yang besar adalah dari sektor industri, mengingat Kota Sukabumi tidak memiliki potensi wisata alam (natural tourism). Pada sektor industri ini, peran pengusaha kecil yang memiliki aktivitas produksi memegang peran penting dalam perekonomian kota. Tujuan penelitian ini adalah untuk mengetahui dan menjelaskan sejauhmana keterampilan manajemen bisnis atau pengelolaan bisnis para pengusaha kecil yang melakukan aktivitas produksi (industri kecil). Penelitian ini menggambarkan elemen-elemen keterampilan pengelolaan  usaha yang dijalankan selama ini. Penelitian ini menggunakan pendekatan kualitatif. Pendekatan ini dimaksudkan untuk mengungkap keterampilan pengelolaan bisnis dari para pengusaha kecil di Kecamatan Cibeureum.  Hasil penelitian menunjukkan bahwa keterampilan pengelolaan bisnis para pengusaha kecil di Kecamatan Cibeureum Kota Sukabumi belum sesuai dengan standar pengelolaan. Artinya masih banyak elemen-elemen pengelolaan bisnis yang tidak berjalan sebagaimana mestinya. Elemen yang paling baik adalah human relations sedangkan yang paling rendah adalah keterampilan akuntansi.Kata kunci: Keterampilan  pengelolaan bisnis, pengusaha kecil